Association of interleukin-4, interleukin-13 gene polymorphisms, HLA-DQ and DR genotypes with genetic susceptibility of type-1 Diabetes Mellitus in Kuwaiti children - Haider, Mohammad Z.; Al Rushood, Maysoun; Alsharhan, Hind; Rasoul, Majedah A.; Al-Mahdi, Maria; Al-Kandari, Hessa (Frontiers in Pediatrics, 2023)
Background: Type-1 diabetes mellitus (T1DM) is a complex multifactorial disease with an autoimmune etiology and is thought to results from an interaction between genetic and non-genetic factors. Cytokines play a crucial role in the pathogenesis of autoimmune diseases due to their effector and regulatory functions in immune responses. Interleukin-4 (IL4) and Interleukin-13 (IL13) are anti-inflammatory cytokines and are considered as important mediators in pathology of the autoimmune diseases. We have determined the genotype frequency of IL4 gene promoter polymorphism (-590C/T, rs2243250), IL13 gene polymorphism p.(Arg130Glu, rs20541) and human leukocyte antigen, HLA-DQ and DR genotypes in Kuwaiti children with T1DM to investigate their role in genetic susceptibility. This study included 261 Kuwaiti children with T1DM and 214 healthy controls. The genotypes for IL4 (-590C/T) and IL13 p.(Arg130Glu) gene polymorphisms were detected by PCR-RFLP methods. HLA-DQ and DR genotypes were determined by sequence-specific PCR methods. Results: The frequency of homozygous CC genotype of the IL4 (-590C/T) gene polymorphism showed a statistically significant association with Kuwaiti T1DM patients (OR 1.64), The homozygous QQ and heterozygous RQ genotypes of IL13 gene polymorphism p.(Arg130Glu), also manifested a statistically significant association with T1DM (OR 2.92 and 4.79). In 55% T1DM patients, the HLA genotype was either DQ2/2 or in combination with a DQ8 allele. Collectively, 91% Kuwaiti T1DM patients had either DQ2 or DQ8 alleles in different combinations highlighting them as the high risk-genotypes. In the case of HLA-DR, the genotypes DR3-5, 3-3, 3-4, 3-7 and 4-4 showed highest frequency amongst the Kuwaiti T1DM patients and thus can be considered as high-risk genotypes. A high degree of co-inheritance (>80%) was detected between IL4 and IL13 gene polymorphism genotypes (CC and QQ) and the high-risk HLA-DQ and DR genotypes amongst the Kuwaiti T1DM patients. Conclusions: We have identified IL4 gene polymorphism (CC) and IL13 gene polymorphism (QQ) as the high-risk genotypes in Kuwaiti T1DM patients. A significant co-inheritance of ‘C’ allele of the IL4 (-590C/T), and ‘Q’ allele of the IL13 p.(Arg130Glu) gene polymorphisms was observed with the high-risk HLA-DQ and DR genotypes which highlight their role in the genetic susceptibility of T1DM in Kuwaiti children.